PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA KELAS XI - Aan Santika; Dewi Surani; Uswatun Khasanah; Ari Fidriyanto (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This study discusses the low ability to solve mathematical problems in mathematics lessons. The results of the process using the PBL (Problem Based Learning) learning model are the focus of research. This study aims to find out whether the PBL model can have an impact on the mathematical problem solving ability of high school students of class XI Algebraic Function Limit material. Using a quasi-experimental method, this study used a non equivqlen control group design as its research. There were 92 students in the study sample. Pretest and posttest written assessments are used to collect data. This investigation revealed that the results on the findings of the Wilcoxon and Mann-Whitney test results displayed a sig value of 0.001<α 0.05 on the use of SPSS. If, Ha is accepted and Ho is rejected. Thus, the results of the Wilcoxcon test and the Mann Whitney test can be concluded that the PBL teaching approach has an impact on some grade XI high school students in mathematical problem solving ability